2020
DOI: 10.1111/1440-1681.13449
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of constrictive pericarditis associated with myocardial fibrosis in rats

Abstract: An efficient animal model is fundamental for studies on the underlying mechanisms of constrictive pericarditis (CP). A novel CP rat model was established by pericardial injection composing of lipopolysaccharides (LPS) and talcum powder without thoracotomy. Pathological changes were confirmed by histological staining. E‐flow Doppler of mitral valve, tissue Doppler E′ in the medial mitral annular (E′sep) and the lateral mitral annular (E′lat) were measured to assess ventricular filling function. Circumferential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 6 A recent animal study confirmed the presence of myocardial fibrosis in an experimental model aimed to primarily induce pericardial constriction. 7 Moreover, myocardial dysfunction appears to play an important role in the pathophysiology of constrictive pericarditis, mainly due to subepicardial involvement of the pericardial process and localized myocardial ischemia, in the setting of high transmural pressures and impairment of coronary blood flow. 8 Since the ventricular apex remains relatively stationary throughout the cardiac cycle, mitral annular assessment allows for measurement of overall longitudinal LV function.…”
Section: Discussionmentioning
confidence: 99%
“… 6 A recent animal study confirmed the presence of myocardial fibrosis in an experimental model aimed to primarily induce pericardial constriction. 7 Moreover, myocardial dysfunction appears to play an important role in the pathophysiology of constrictive pericarditis, mainly due to subepicardial involvement of the pericardial process and localized myocardial ischemia, in the setting of high transmural pressures and impairment of coronary blood flow. 8 Since the ventricular apex remains relatively stationary throughout the cardiac cycle, mitral annular assessment allows for measurement of overall longitudinal LV function.…”
Section: Discussionmentioning
confidence: 99%